A marriage of inconvenience: Miriam Makeba's relationship with Stokely Carmichael and her music career in the United States. Issue 3 (2nd July 2016) - Fleming, Tyler
Abstract: This article analyzes the career of famed South African singer, Miriam Makeba, in the United States. After finding success throughout much of the 1960s, Makeba's career and public image shifted after her 1968 marriage to Stokely Carmichael, a noted Civil Rights activist and proponent of the Black Power movement. Once Makeba became associated with Carmichael and his reputation as an extremist, the American public, media, and music industry changed their approach to Makeba as an individual and as an artist throughout the late 1960s and 1970s. Ultimately, this union caused American audiences to turn on her and her music, and this essay explores how and why this shift occurred.